2020
DOI: 10.1371/journal.pone.0236013
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the organizational, environmental, professional and child and family factors influencing the timing of admission to hospital for children with serious infectious illness

Abstract: Background Infection, particularly in the first 5 years of life, is a major cause of childhood deaths globally, many deaths from infections such as pneumonia and meningococcal disease are avoidable, if treated in time. Some factors that contribute to morbidity and mortality can be modified. These include organisational and environmental factors as well as those related to the child, family or professional. Objective Examine what organizational and environmental factors and individual child, family and professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…While some parents reported being given precise information about symptoms, such as “ sucking in at the ribs ”, others reported simply being told to come back if “ it gets worse ” or “ if you are worried ” – neither instruction was sufficiently detailed to enable parents to know when was worse enough or how much more worried they needed to be (given that they were already worried enough to seek help). Knowledge and experience influenced parents’ decision making as seen in other research(13, 19, 33). Research has found that safety netting information needs to provide information on how to assess the severity of symptoms for all the child’s symptoms, supported by information on how to care for the child and in written or recorded format(28, 40, 41).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…While some parents reported being given precise information about symptoms, such as “ sucking in at the ribs ”, others reported simply being told to come back if “ it gets worse ” or “ if you are worried ” – neither instruction was sufficiently detailed to enable parents to know when was worse enough or how much more worried they needed to be (given that they were already worried enough to seek help). Knowledge and experience influenced parents’ decision making as seen in other research(13, 19, 33). Research has found that safety netting information needs to provide information on how to assess the severity of symptoms for all the child’s symptoms, supported by information on how to care for the child and in written or recorded format(28, 40, 41).…”
Section: Discussionmentioning
confidence: 57%
“…Such criticism was reported to delay help seeking to avoid further criticism from those in positions of power (24-30). Parents want to manage the impression they make on others as morally good parents and as good citizens who use services appropriately, reflecting prior research (13, 24, 26, 29-31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4-hour A&E target (95% of patients addressed within 4 hours) has not been achieved since 2013 [19], highlighting the current strain on urgent-care hospital resources. A review of factors affecting these behaviors found a range of different reasons, including (among others): parents' uncertainty and lack of confidence around recognizing problematic symptoms or evaluating their child's condition; mistrust of, or previous negative experiences with, clinicians; concerns about wasting clinicians' time; and being perceived negatively by clinicians [20]. This demonstrates the need for better access to primary care services or community-based support for acute pediatric illness and efforts to improve parental health literacy and confidence in determining whether, or which, treatment services are appropriate when a child is ill and how best to manage acute childhood illnesses [1,10,13].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The 4-hour A&E target (95% of patients addressed within 4 hours) has not been achieved since 2013 [ 19 ], highlighting the current strain on urgent-care hospital resources. A review of factors affecting these behaviors found a range of different reasons, including (among others): parents’ uncertainty and lack of confidence around recognizing problematic symptoms or evaluating their child’s condition; mistrust of, or previous negative experiences with, clinicians; concerns about wasting clinicians’ time; and being perceived negatively by clinicians [ 20 ].…”
Section: Introductionmentioning
confidence: 99%